Women’s Fatwa-Making in Indonesia: Gender, Authority, and Everyday Legal Practice - Ismah, Nor (International Journal of Islam in Asia, 2023)
My article proposes a new approach to the study of fatwas (Islamic legal opinion) in an Indonesian context, aiming at contributing to Islamic Studies on fatwa-making more broadly. By combining an Islamic studies framework with anthropological research and gender studies, my article challenges the traditional focus on male-dominated institutions and emphasizes the everyday practice of issuing fatwas at the grassroots level, particularly by women. I argue that fatwa-issuing institutions are gendered, excluding women from significant positions and recognition as Islamic scholars. Therefore, studying women’s fatwa-making requires considering various sites of interaction between female mufti and fatwa seekers. These interactions showcase dynamic changes in women’s experiences, religious authority, and everyday fatwa-making practices, driven by context-specific resources. Women’s participation disrupts traditional norms, challenging gendered structures in fatwa-making institutions. Moreover, it signifies the evolution of doctrinal changes and ethical practices, redefining fatwas from static outcomes to a dynamic and inclusive realm of interaction, innovation, and Islamic authority.